2004
DOI: 10.1094/pdis.2004.88.4.316
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Tilletia indica Teliospores in Different Soils

Abstract: To determine the potential for Tilletia indica, cause of Karnal bunt of wheat, to survive and become established in new areas, a teliospore longevity study was initiated in Kansas, Maryland, Georgia, and Arizona. Soil from each location was infested with T. indica teliospores and placed in polyester mesh bags. The bags were placed within soil from the same location within polyvinyl chloride pipes. Pipes were buried in the respective plots such that the bags were at 5-, 10-, and 25-cm depths. Each pipe was open… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 8 publications
3
20
0
Order By: Relevance
“…However, the link between survival of buried teliospores and potential distribution of Karnal bunt is unproven and tenuous. Similar longevity experiments have been undertaken in Arizona, Georgia, Kansas, Maryland and Montana and viable teliospores were recovered after burial for long periods (Babadoost et al 2004;Bonde et al 2004a, b). It is highly likely that teliospores of T. indica can survive for extended periods in soils at locations where the pathogen is never going to establish.…”
Section: Teliospore Factors Influencing Disease Establishmentsupporting
confidence: 54%
“…However, the link between survival of buried teliospores and potential distribution of Karnal bunt is unproven and tenuous. Similar longevity experiments have been undertaken in Arizona, Georgia, Kansas, Maryland and Montana and viable teliospores were recovered after burial for long periods (Babadoost et al 2004;Bonde et al 2004a, b). It is highly likely that teliospores of T. indica can survive for extended periods in soils at locations where the pathogen is never going to establish.…”
Section: Teliospore Factors Influencing Disease Establishmentsupporting
confidence: 54%
“…The percentage germination of recovered teliospores was also significantly affected by some soil sources at the end of the 32-month experimental period (Babadoost et al, 2004). A decrease in teliospore recovery and percentage germination was also noted by Bonde et al (2004a, b), who found significant differences in survival when teliospores were incubated in different soils from different regions of the US. Numbers of viable teliospores recovered from soils from Maryland and Kansas over time were much less than from soils from Arizona.…”
Section: Dissemination Of Karnal Bunt and Implications For Potential mentioning
confidence: 70%
“…This could lead to their death and disintegration (Babadoost, Mathre, Johnston, & Bonde, 2004). A marked decrease in the percentage of extractable teliospores has been observed after 6 months (Bonde et al, 2004a). However, whether this is caused by spore breakdown, germination followed by breakdown, or the adherence of spores to soil particles during extraction has not been determined.…”
Section: Dissemination Of Karnal Bunt and Implications For Potential mentioning
confidence: 99%
“…Because of its international quarantine status, it has the potential for causing economic losses. Presently, 77 countries have restrictions on importing wheat from the areas where the disease occurs (Bonde et al, 2004). Being a seed-, soil-, and airborne pathogen, it is very difficult to manage once introduced to an area.…”
Section: Introductionmentioning
confidence: 99%